2023
DOI: 10.3390/antibiotics12091432
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Pathogens of Wound Infection in Burn Inpatients from East China

Siqi Zhou,
Shuzhen Xiao,
Xuedong Wang
et al.

Abstract: Background: Infection is the predominant contributor to morbidity and mortality in burn patients, and burn wound infection (BWI) is the most common reason. The objective of this research was to analyze the incidence, factors and progression of BWI, in terms of events and bacteria. Methods: Clinical variables of all qualified patients admitted to burn wards were analyzed retrospectively in 2021 at a tertiary hospital in eastern China through univariate analysis and multivariate logistic regression. The Kaplan–M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…[ 27 ] 2016–20 Henan Tertiary Unclear 1902 584 278 69 137 124 7 Zhou et al. [ 13 ] 2021 Shanghai Tertiary 348 649 102 55 69 69 92 8 Han et al. [ 28 ] 2010–23 Shaanxi Tertiary 216 245 101 54 33 8 - 6 Hu and Lu [ 29 ] 2020–22 Jiangsu Tertiary Unclear 1167 215 292 192 247 6 Han and Zhang [ 30 ] 2015–20 Chongqing Tertiary 833 833 134 103 65 63 49 7 Li et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 27 ] 2016–20 Henan Tertiary Unclear 1902 584 278 69 137 124 7 Zhou et al. [ 13 ] 2021 Shanghai Tertiary 348 649 102 55 69 69 92 8 Han et al. [ 28 ] 2010–23 Shaanxi Tertiary 216 245 101 54 33 8 - 6 Hu and Lu [ 29 ] 2020–22 Jiangsu Tertiary Unclear 1167 215 292 192 247 6 Han and Zhang [ 30 ] 2015–20 Chongqing Tertiary 833 833 134 103 65 63 49 7 Li et al.…”
Section: Resultsmentioning
confidence: 99%
“…The colonization patterns of pathogens that cause burn infections may vary owing to differences in geographical, climatic and environmental factors, hospital management practices and the duration of hospitalization. A study conducted in Morocco identified Acinetobacter baumannii and Pseudomonas aeruginosa as the most common pathogens among patients with burn infection, while studies in China revealed that Staphylococcus aureus and Staphylococcus epidermidis were the most prevalent pathogens isolated from patients with burn injuries [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By the growth of microorganisms in the initially‐sterile burn wounds, infection would then occur depending on the wound's nature and extension and microorganism's species and number. 4 Pseudomonas aeruginosa as a leading factor in the induction of serious infections over the wound. 5 P. aeruginosa is indeed among the top 10 virulent nosocomial pathogens worldwide.…”
Section: Introductionmentioning
confidence: 99%